Home Browse Journal Info Guide for Authors Submit Manuscript Reviewers Contact Us The Impact of Genre-Based Instruction Treatments on EAP Students’ Writing Quality - Sayyed Mohammad Alavi; Majid Nemat; Sedigheh Karimpour (Journal of Modern Research in English Language Studies)
The last decade has seen an increasing attention given to the notion of genre-based instruction, its application and efficacy in language teaching and learning. Regarding the benefits of genre-based instruction in second language acquisition, there have been ongoing debates in pedagogical treatments associated with genre-based instruction in various educational contexts. The purpose of the current study was to examine how three genre-based instruction treatments affected medical students’ use of key features of the medical case report. A group of 150 subjects were selected from EFL medical students in Mazandaran University of Medical Sciences. Both male and female students were invited to this study. These students did not previously receive any genre-based instruction before the study. The participants were assigned to the “Experimental Group One”, “Experimental Group Two” and “Control” groups. The scores from the students’ pre -and post -essays were used to find out whether the students improved their writing from the pre- to post- tests. The groups were taught for one academic semester which consisted of 15 weeks. The analysis of pre- and post-essays showed that there was a significant difference in the writing qualities of explicit and implicit genre-based instruction groups. The students in the experimental groups actually outperformed on most genre move categories assessed in the posttests. Researchers and educators could benefit from an experimental study of the development of genre awareness through models with explicit and implicit writing instruction.